Pengaruh Model Problem Based Learning Berbantuan Video Based Laboratory Terhadap Hasil Belajar Peserta Didik Pada Materi Alat-Alat Optik - Riyanti, Nandita Agus; Sutrio, Sutrio; Wahyudi, Wahyudi; Kosim, Kosim (Kappa Journal, 2023)
This research aims to determine the effect of the problem based learning model assisted by video based laboratory on student learning outcomes in the material of optical devices. The population in this research were all class XI MIPA SMAN 1 Gunungsari. Sampling was carried out using a purposive sampling technique, so that class XI MIPA 4 was obtained as the experimental class and class XI MIPA 1 as the control class. The design used in this research was the nonequivalent control group design, where the two samples were given different treatment. The experimental class will be given learning treatment using a problem based learning model assisted by video based laboratory, while the control class will be given treatment with conventional learning. Learning outcomes are measured, namely in the cognitive domain which includes cognitive levels from C1 to C6. The instrument used was a multiple choice test with 20 questions. Study result data were analyzed using parametric statistics, namely t-test polled variance with a significant level of 5% or 0.05 and obtained a tcount of 2.49 and a ttable of 2.01. If tcount is greater than ttable, then Ho is rejected and Ha is accepted, so it can be concluded that the video based laboratory assisted problem based learning model has an effect on student learning outcomes in the material of optical devices.